Sengketa Pemakaian Merek INTERCO Berdasarkan Putusan Pengadilan Niaga Pada Pengadilan Negeri Medan No. 1/Pdt.Sus.HKI/Merek/2020/PN Niaga Mdn jo Putusan Mahkamah Agung No. 1333K/Pdt.Sus-HKI/2021 - Rachmatullah Rachmatullah; OK Saidin; Jelly Leviza; Mahmud Mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2022)
The Ministry of Law and Human Rights or the Directorate General of Intellectual Property or the Directorate of Marks and Geographics must be careful before accepting a trademark registration by following the applicable laws and regulations that adhere to the first to file principle so that there is no registration of the same mark